Pengaruh Literasi Keuangan terhadap Intensi Berwirausaha dengan Pengetahuan Technopreneurship sebagai Variabel Moderasi - Ainun Novita Anggraini; Norida Canda Sakti (Lembaga Pengembangan Kinerja Dosen, 2025)
Entrepreneurship plays an important role as a driving force in a country's economic development. University students, as prospective graduates, have great potential to develop into creative and independent young entrepreneurs. Therefore, it is important to explore the factors that influence the emergence of entrepreneurial intent among students. This study aims to examine the extent to which financial literacy influences entrepreneurial intent, as well as to investigate whether knowledge of technopreneurship can strengthen this relationship as a moderating variable. This study employs a quantitative approach with data analysis using the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique with the assistance of WarpPLS software. The respondents in this study consisted of 81 students from the Economics Education Program, Faculty of Economics and Business, Surabaya State University, class of 2021. The results of the study indicate that financial literacy has a positive and significant influence on students' entrepreneurial intentions. In other words, the higher the level of financial literacy among students, the greater their desire to enter the world of entrepreneurship. However, technopreneurship knowledge does not play a moderating role in this relationship. This indicates that technopreneurship knowledge is largely conceptual and has not yet been applied in actual entrepreneurial activities.